Study of Multi-drug Resistant Mechanism inAcinetobacterbaumannii Isolated From Nosocomial Infections in Educational Ramadi Hospital - M. Hassan, Omar; A. Saleh, Thaer; A. Mohaemeed, Abdulkhaliq (Iraqi Journal of Science, 2023)
In this study, A 320 clinical specimens were collectedfromIntensiveCareUnits, Surgery and burn units in educational Ramadihospital. The enrichment and isolation of A. baumannii from collectedspecimens led to isolate 30 bacterial strains from 337 bacterial isolates withrate (8.9%), which similar in morphology for that standard strains. The rateof A. baumannii isolated from burn specimens was 80%, the wound specimens (13.33%), and sputum (6.67% The study detect resistance of A.baumanniifor different antibiotics, All isolates showed multidrug resistant,the isolates was 100% resistant for Ampicillin, Cefazolin, Cefotaxime,Cloxacillin, Colistin and Trimethoprim, as showed high resistance tocarbapenems reached to 80%, but it showed low resistance (20%) againstLevofloxacin. So 100% of A. baumanniiisolates (n=30) were producedAmpC β-Lactamases which hydrolyze a broad-spectrum of cephalosporins,and 60% from isolates (n=18) were producedMetalo β-Lactamases (MBL)which hydrolyze a broad array of antimicrobial agents, includingcarbapenems.